Self-Reported Symptoms of Infection Among Travelers Departing From Sydney and Bangkok Airports - Heywood, A.; Watkins, Rochelle; Pattanasin, S.; Iamsirithaworn, S.; Nilvarangkul, K.; Macintyre, C. (Wiley-Blackwell Publishing, Inc., 2010)
Background. Data on the burden of illness in travelers departing from both developing and developed countries within the Asia-Pacific region is scarce. We conducted a survey to assess symptoms of infection among travelers within the region. Methods. A self-administered questionnaire was distributed to travelers departing Sydney airport, Australia, for destinations in Asia and departing Bangkok Airport, Thailand, for Australian destinations during the respective winter months of 2007. A two-stage cluster sampling technique was developed to ensure representativeness and a weighting was applied to the Sydney sample. Travelers were assessed for symptoms of infection (fever, sore throat, diarrhea, rash, and myalgia), travel activities, and social contact in the 2 weeks prior to departure.Results. A total of 843 surveys was included in the final sample (Sydney 729, response rate 56%; Bangkok 114, response rate 60%). Overall, 45.6% of respondents were Australian residents and 26.7% were residents of countries in Asia. At least one symptom of infection was reported by 23.8% of respondents and 5.4% reported two or more symptoms of infection in the 2 weeks prior to departure. The proportion reporting symptoms was higher in those departing Bangkok compared to Sydney. Significant risk factors for the reporting of symptoms differed between residents and visitors departing each study site. Activities resulting in high rates of social contact prior to travel, particularly contact with febrile persons, were found to be independent predictors of reported symptoms. Conclusions. Self-reported symptoms of infection were common in our sample of travelers. Infectious diseases in travelers can result in spread across international borders and may be associated with the frequency of social contacts and reported illness among travelers.